Chapter Corpi annidati - Robinson, Sarah (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2021)
We are bodies start from other bodies. Yet, we rarely consider how our bodies extend into our surroundings. Discusses our body schema, peripersonal and extra personal space. Considers buildings as extensions of our bodies and minds and develops the con-cept of nested bodies that engage the senses, spatial cognition and a sense of place, audi-tory system and acoustic architecture, the haptic system and texture, tasting, smelling and the imagination, visual perception and chronobiology, atmospheric space.